2021
DOI: 10.3389/fimmu.2021.678964
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus Macaque Activating Killer Immunoglobulin-Like Receptors Associate With Fc Receptor Gamma (FCER1G) and Not With DAP12 Adaptor Proteins Resulting in Stabilized Expression and Enabling Signal Transduction

Abstract: Activating killer cell immunoglobulin-like receptors (KIR) in macaques are thought to be derived by genetic recombination of the region encoding the transmembrane and intracellular part of KIR2DL4 and a KIR3D gene. As a result, all macaque activating KIR possess a positively charged arginine residue in the transmembrane region. As human KIR2DL4 associates with the FCER1G (also called Fc receptor-gamma, FcRγ) adaptor, we hypothesized that in contrast to human and great ape the activating KIRs of macaques associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…For FCER1G we noticed an increase in rhCMV+ macaques which missed statistical significance ( Figure 4 ). Contrasting human NK cells is the usage of the FCER1G -encoded FcR-gamma protein as the adaptor molecule for activating KIR in rhesus macaques ( 20 ). Therefore, downregulation of this adaptor may not be expected as this would thwart aKIR+ NK cells in rhesus macaques.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For FCER1G we noticed an increase in rhCMV+ macaques which missed statistical significance ( Figure 4 ). Contrasting human NK cells is the usage of the FCER1G -encoded FcR-gamma protein as the adaptor molecule for activating KIR in rhesus macaques ( 20 ). Therefore, downregulation of this adaptor may not be expected as this would thwart aKIR+ NK cells in rhesus macaques.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to human adaptive NK cells that are further characterized by strongly decreased FCER1G expression ( 9 , 18 ), we found slightly increased transcription of FCER1G in rhCMV+ rhesus macaques as compared to rhCMV- animals ( Figure 4 ). The most probable reason for this difference between human and rhesus macaque adaptive NK cells is that macaques use FCER1G as adapter protein for their stimulatory KIR receptors and not DAP12 ( 20 ) as in human NK cells and, therefore, rely on continued expression of this adaptor protein. However, a report by Shah and colleagues describes a subpopulation of rhesus macaque NK cells that lacks expression of the FCER1G -encoded FCR-gamma adapter protein and expands in rhCMV-infected rhesus macaques ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a component of the high affinity immunoglobulin E (IgE) receptor involved in the transduction of allergic inflammatory signals in mast cells. It had been proved that it was expressed in monocytes/macrophages of tumor microenvironment 30 , 31 . Studies had shown that the subgroup with higher myeloma expression level had better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by their nomenclature, KIRs typically have two or three extracellular Ig-like domains (2D or 3D) and either long (L) or short (S) cytoplasmic tails. KIRs with long cytoplasmic tails contain a pair of ITIMs that transduce inhibitory signals, whereas those with short cytoplasmic tails associate with adaptor molecules such as DAP12 or FcεRIγ to transduce activating signals (2, 3). Inhibitory KIRs normally suppress NK cell responses through interactions with MHC class I ligands on the surface of heathy cells.…”
Section: Introductionmentioning
confidence: 99%